Stress and job satisfaction among nursing faculties in academic institutions in Nepal: A cross-sectional comparison between government and private institutions - Jamuna Bhattarai; Muna Rana; Subhadra Khakurel; Usha Yadav; Heema Sunar (PLoS ONE, 2025)
Background Stress and job dissatisfaction are significant factors leading to reduced efficiency and loss of human resources in all sectors, especially nursing education. This study aimed to compare the levels of stress, and job satisfaction among nursing faculty members in government and private colleges in Nepal. Methods A cross-sectional study design was employed and conducted across nursing colleges in both the government and private sectors of Nepal. A total of 576 faculties were conveniently recruited from 13 government colleges and 26 private colleges for this study. The data were summarized using descriptive and inferential statistics, comparing the results between the faculties of the government and the private colleges. Results Among the 576 respondents, 24.7% reported high levels of stress, while the majority (62.7%) were ambivalent about their job and less than one-third were satisfied. The majority of the respondents working in government colleges reported lower stress levels. Regarding job satisfaction, 8.9% of respondents were dissatisfied, and 30.7% were satisfied in government colleges, which was 2% higher than in private colleges. More than half of the respondents were ambivalent about their jobs in both private (63.7%) and government colleges (60.3%). The levels of stress, and job satisfaction did not significantly differ between government and private colleges. Conclusions Stress levels are slightly higher in private colleges, while faculty members in government colleges report greater job satisfaction. Future research could be directed towards the identification of ways to reduce stress and promote satisfaction among nursing faculties, especially in private colleges.